Ethics of Discussion and Debate in the Perspective of Constitutional Law Norms - Renita Indriani Hasibuan; Fahrezi Zulnavar; Atthariq Zainadine (ISNU Sumatera Utara, 2025)
Discussion and debate are important instruments in the formation, testing, and development of legal norms. In legal practice, especially in the realm of constitutional and academic law, discourse not only functions as a means of exchanging ideas, but also as a mechanism for searching for rational and just truth. However, without a clear ethical foundation, discussion and debate have the potential to lose their constructive value and instead lead to normative and social conflicts. Therefore, the study of the ethics of discussion and debate from the perspective of legal norms is relevant and urgent. This research aims to analyze the concept, function, and urgency of ethical discussion and debate as part of legal norms, paying attention to the historical, academic, and ethical dimensions that develop in the legal tradition, including Islamic perspectives. The research method used is qualitative research with a descriptive-analytical approach, through literature studies of relevant legal literature, ethics, and Islamic thought. The results and discussions show that the ethics of discussion and debate are a manifestation of legal norms that function to maintain rationality, justice, and respect for differences of opinion. This ethics plays an important role in ensuring that legal discourse takes place in an argumentative, objective, and dignified manner. Thus, the application of the ethics of discussion and debate not only strengthens the quality of legal thought, but also supports the creation of a healthy and civilized legal culture.